Steady steps versus sudden shifts: Cooperation in (a)symmetric linear and step-level social dilemmas - Judith Kas; David J. Hardisty; Michel J. J. Handgraaf (Judgment and Decision Making, 2021)
Are groups of people better able to minimize a collective loss if there is a collective target that must be reached or if every small contribution helps? In this paper we investigate whether cooperation in social dilemmas can be increased by structuring the problem as a step-level social dilemma rather than a linear social dilemma and whether cooperation can be increased by manipulating endowment asymmetry between individuals. In two laboratory experiments using ‘Public Bad’ games, we found that that individuals defect less and are better able to minimize collective and personal costs in a step-level social dilemma than in a linear social dilemma. We found that the level of cooperation is not affected by an ambiguous threshold: even when participants cannot be sure about the optimal cooperation level, cooperation remains high in the step-level social dilemmas. We find mixed results for the effect of asymmetry on cooperation. These results imply that presenting social dilemmas as step-level games and reducing asymmetry can help solve environmental dilemmas in the long term.